Analisis Kinerja Guru Terhadap Prestasi Belajar Siswa - Safitri, Mirawati; Iqbal, Muhammad; Hariawan, Rudi (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2024)
Abstract: This study aims to analyze the influence of teacher performance on student learning achievement. The type of research is quantitative with teacher performance as the independent variable (x), and student learning achievement as the dependent variable (y). This study uses a sample of 100 students from a population of 426 using proportional random sampling. Data collection techniques use questionnaires and documentation methods as supporting methods. Data analysis methods use descriptive statistical analysis and simple linear regression analysis. Based on the results of descriptive analysis, teacher performance with a good category is 45% of teachers, 53% of teachers with a sufficient category, and only 2% with a less category. While for student learning achievement with a category of minimum completion criteria value (KKM-75) in mathematics subjects, there are 82% of students, and around 18% of students with a category of not yet complete. Based on the results of the t-test which showed a significant value of 0.006 < 0.05 with a coefficient of determination R2 = 0.075, which means it can be concluded that there is a significant influence of teacher performance on student learning achievement in Senior High School 1 Sakra Timur Academic Year 2023/2024. In other words, it can be described that the better the performance of a teacher during the learning process can have a positive effect on improving student learning achievement.Key Words: Teacher Performance, Learning AchievementAbstrak: Penelitian ini bertujuan untuk menganalisis pengaruh kinerja guru terhadap prestasi belajar siswa. Jenis penelitian ini adalah kuantitatif dengan kinerja guru sebagai variabel bebas (x) dan prestasi belajar siswa sebagai variabel terikat (y). Penelitian ini menggunakan penelitian sampel sebanyak 100 siswa dari 426 populasi dengan menggunakan teknik proportional random sampling. Teknik pengumpulan data primer menggunakan metode angket dan dokumentasi sebagai pendukung. Metode analisis data menggunakan analisis statistik deskriptif, dan analisis regresi linier sederhana. Berdasarkan hasil analisis deskriptif bahwa kinerja guru dengan kategori baik yang berjumlah 45% guru, 53% guru dengan kategori cukup, dan hanya 2% katergori kurang. Sedangkan untuk prestasi belajar siswa dengan kategori nilai kriteria ketuntasan minimal (KKM-75 pada mata pelajaran matematika sebanyak 82% siswa, dan sekitar 18% siswa dengan kategori tidak tuntas. Berdasarkan hasil uji-t yang menunjukan nilai signifikan sebesar 0.006 < 0.05 dengan nilai koefisien determinasi R2 = 0.075 yang berarti dapat disimpulkan bahwa terdapat terdapat pengaruh positif yang signifikan kinerja guru terhadap prestasi belajar siswa di SMAN 1 Sakra Timur Tahun Pelajaran 2023/2024. Dengan kata lain dapat dideskripsikan bahwa semakin baik kinerja seorang guru selama proses pembelajaran dapat berpengaruh positif terhadap peningkatan prestasi belajar siswa.Kata Kunci: Kinerja Guru, Prestasi Belajar